2021
DOI: 10.1093/jas/skab058
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity vs. monotony: the effect of a multiforage diet as opposed to a single forage diet on animal intake, performance, welfare, and urinary nitrogen excretion

Abstract: The objective of this study was to determine the effect of offering animals a multi-forage choice of fresh herbages on dry matter intake (DMI), live weight gain and animal welfare, in comparison with a monotonous diet of ryegrass (Lolium perenne L.). Twenty ram lambs [30.5 ± 0.9 kg initial live weight; mean ± standard error of the mean], were randomly allocated to either a diet consisting of diverse multi-forage choice (MF) or a single forage ryegrass (SF) diet (n = 10 per treatment) for 35 days. Both diets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The DIV and VAR lambs both had greater ADG than the SFA, largely explained by differences in the nutritional composition of the diet, namely, the greater DMD and ME content of the DIV and VAR diets. Other studies have reported similar results with lower DMI from treatments offered a flavorally or biochemically uniform diet compared to those offered choice from a diverse range of feeds (Keskin et al, 2004;Atwood et al, 2006;Distel et al, 2007;Villalba et al, 2011;Garrett et al, 2021). The magnitude of the effect from choice of diverse feeds on increased DMI is lower within the present study than that reported in other studies.…”
Section: Intake and Performance: Sfa Vs DIV And Varsupporting
confidence: 76%
See 3 more Smart Citations
“…The DIV and VAR lambs both had greater ADG than the SFA, largely explained by differences in the nutritional composition of the diet, namely, the greater DMD and ME content of the DIV and VAR diets. Other studies have reported similar results with lower DMI from treatments offered a flavorally or biochemically uniform diet compared to those offered choice from a diverse range of feeds (Keskin et al, 2004;Atwood et al, 2006;Distel et al, 2007;Villalba et al, 2011;Garrett et al, 2021). The magnitude of the effect from choice of diverse feeds on increased DMI is lower within the present study than that reported in other studies.…”
Section: Intake and Performance: Sfa Vs DIV And Varsupporting
confidence: 76%
“…Monotonous feeding environments impose nutritional repetition, which may impair animal performance and welfare. Monotonous diet presentation reduces intake or productivity relative to animals provided choice from a diverse diet (Provenza et al, 2007;Rodríguez et al, 2007;Dixon and Pasinetti, 2010;Garrett et al, 2021). This can be the result of nutrient specific satiation, as the upper threshold for a specific nutrient is reached despite deficiencies in other nutrients existing (Raubenheimer, 1992;Early and Provenza, 1998;Gregorini et al, 2017), or sensory-specific satiety, where the repeated oro-sensorial experience (i.e., taste) saturates the intake-related sensorial neurons and reduces the response for a particular feed (Early and Provenza, 1998;Epstein et al, 2009;Gregorini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary and management strategies focusing on diverse swards and grazing management have been extensively explored as ways to reduce N losses [ 4 , 16 , 17 , 18 , 19 ], with the use of narrow-leaf plantain ( Plantago lanceolata L. (PL)) showing promising results for reducing total N excretions and UN concentrations in dairy cows [ 20 , 21 ]. PL is known to contain secondary bioactive compounds, such as acubin, catalpol, and acteoside [ 22 , 23 ], that have been reported to have antimicrobial and diuretic effects [ 22 , 24 ], which may influence the N partitioning of the animals.…”
Section: Introductionmentioning
confidence: 99%